KAJIAN PSIKOANALISIS NOVEL BURUNG TERBANG DI KELAM MALAM KARYA ARAFAT NUR DAN KESESUAIANNYA SEBAGAI MATERI PEMBELAJARAN SASTRA PADA JENJANG SMA DI KOTA BANDA ACEH - Wahidah Nasution; Indratmoko Ariwibowo (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2016)
This study aims to: (1) describe the elements of the novel entitled “Burung Terbang di Kelam Malam karya Arafat”; (2) describe the main character(3) describe the connection of the novel as a literary learning materials at the high school in the city of Banda Aceh. This is a qualitative study used psychoanalytical approach. The activities are read, observe, interpret and analyze the novel. The results of these activities are described in the form of sentences. Research conducted approximately six months, started on February 2016 to August 2016. The source of data in this study are: (1)the text of the novel Burung Terbang di Kelam Malam karya Arafat published by Bentang Pustaka Yogyakarta in 2014, 374 pages; (2) field notes which consists of two parts, namely the description and reflection which aimed to describe the object being studied, (3) the books related to the study; (4) the interview with Indonesian teachers. Interactive techniques was used as the technique of collecting data. The results showed: (1) the structure of novel related the theme, point of view, characterization, setting, and the groove; (2) psychoanalysis key figures related to the id, ego and super-ego; (3) The Novel can be utilized as learning materials of literature subject at the high school level.